Law and the Visible - Umphrey, Martha Merrill; Douglas, Lawrence; Sarat, Austin (Book collections on Project MUSE., 2021)
"If you take a video of police officers beating a Black man into unconsciousness, are you a witness or a bystander? If you livestream your friends dragging the body of an unconscious woman and talking about their plans to violate her, are you an accomplice? Do bodycams and video doorbells tell the truth? Are the ubiquitous technologies of visibility open to interpretation and manipulation? These are just a few of the questions explored in the rich and broadly interdisciplinary essays within this volume, Law and the Visible, the most recent offering in the Amherst Series for Law, Jurisprudence, and Social Thought. Individual essays discuss the culpability of those who record violence, the history of racialized violence as it streams through police bodycams, the idea of digital images as objective or neutral, the logics of surveillance and transparency, and a defense of anonymity in the digital age. Contributors include Benjamin J. Goold, Torin Monahan, Kelli Moore, Eden Osucha, Jennifer Peterson, and Carrie A. Rentschler"--